THU0302 Histology findings in giant cell arteritis (GCA) and their relationship with the ultrasound results: analysis of data from the tabul study (temporal artery biopsy vs ultrasound in diagnosis of giant cell arteritis). (15th June 2017) - Ponte, CB; Monti, S; Singh, S; Hutchings, A; Diamantopoulos, A; Dasgupta, B; Schmidt, WA; Luqmani, RA
Abstract : Background: Although temporal artery biopsy (TAB) has been the gold standard for diagnosis of GCA, ultrasound has superior sensitivity but lower specificity. Occasionally, histological evidence of inflammation is restricted to the vasa vasorum, the periadventitial small vessels, or both, which could limit the diagnostic sensitivity of ultrasound for GCA. Moreover, false positive ultrasound results have been described in patients with arteriosclerosis on histology. Objectives: To compare histologic findings with ultrasound results from patients with suspected GCA included in the TABUL study (a multinational study to assess the relative performance of ultrasound and TAB for diagnosing GCA). Methods: All patients with newly suspected GCA underwent an ultrasound of both temporal and axillary arteries, followed by a TAB, within 7 days of commencing glucocorticoid therapy. TAB pathological diagnoses were analysed and the different histologic features were compared with the ultrasound results using Chi-square or Fisher exact tests. Results: Results for TAB and ultrasound were available in 388 patients (69% with a final clinician's diagnosis of GCA). An artery was definitely obtained in 363 (94%) TABs; the pathological diagnosis was GCA in 104 (29%) cases, arteriosclerosis in 35 (10%), normal in 203 (56%) and other conditions in 21 (6%). All TABs compatible with GCA also had a final clinician's diagnosis of GCA (73% with positive ultrasound). Table 1 shows that ultrasound positivity occurred more frequently in patients where the media was the predominant site of inflammation (p=0.01). The ultrasound result was positive in 9 (26%) cases where TAB was consistent with arteriosclerosis, 8 (89%) of whom had a final clinician's diagnosis of GCA. The ultrasound was positive in 64 (32%) cases where TAB was normal, 52 (81%) of whom had a final clinician's diagnosis of GCA. Conclusions: Amongst patients with suspected GCA, ultrasound is more likely to be positive when histological inflammation is predominantly present in the intima-media. No significant correlation between histologic findings and negative ultrasound results was found, but the small number of cases with predominant vasa vasorum infiltrates in our cohort limited this analysis. There was only one false positive ultrasound in patients with arteriosclerosis on TAB. Disclosure of Interest: None declared